In-situ O-isotope analysis of relict spinel and forsterite in small (<200 μm) Antarctic micrometeorites – Samples of chondrules & CAIs from carbonaceous chondrites. (15th May 2022) - Rudraswami, N.G.; Suttle, M.D.; Marrocchi, Y.; Taylor, S.; Villeneuve, J.
Abstract: We report high-precision secondary ion mass spectrometer triple oxygen isotope systematics (95 individual analyses) from 37 micrometeorites (MMs) collected from South Pole Water Well (SPWW), Antarctica. The study population focuses on unmelted coarse-grained (Cg) MMs ( n = 23) with both multiple ( n = 14) and single-mineral ( n = 9) varieties investigated. We also analysed relict minerals in porphyritic cosmic spherules ( n = 13) and the relict matrix in a single scoriaceous fine-grained (Fg) MM. The target minerals investigated are primarily olivine (Fo ∼ 43–99%) and spinel. Textural, chemical and isotopic data confirm that both olivine and spinel grains have retained their pre-atmospheric O-isotope compositions, allowing inferences to be drawn about their formation and parent body affinities. We separate the study population into three groups: spinel-free particles (consisting of the CgMMs and PO cosmic spherules), spinel-bearing MMs and the single FgMM. Olivine grains in spinel-free MMs vary between δ 17 O: −12.6‰ and +3.5‰, δ 18 O: −9.6‰ and +7.5‰, and Δ 17 O: −9.5‰ and +1.3‰ and define a slope-1 profile in δ 18 O–δ 17 O isotope space. They are most likely fragmented chondrules, with both type I and type II varieties represented. Their observed Mg#-Δ 17 O distribution is best explained by a mixture of CM chondrules and either CR chondrules, Tagish Lake chondrules or WILD2 cometary silicates. One of these chondrule-like MMs has an isotopically heterogeneous composition, characterised by a single olivine grain with a markedly 16 O-rich composition (Δ 17 O: −16.3‰), suggesting it is a relict silicate fragment of AOA material that was incorporated into the chondrule precursor. We analysed 11 spinel grains in five spinel-bearing MMs. In all instances spinels are nearly pure MgAl2 O4 with isotopically light ( 16 O-rich) compositions (ranging from δ 17 O: −34.4‰ to −0.9‰, δ 18 O: −30.8‰ to +11.0‰, and Δ 17 O: −18.3‰ to −4.4‰). They are therefore 16 O-poor relative to spinel found in unaltered CAIs, indicating a different origin. Grains with high Cr2 O3 contents (>0.5 wt.%) are interpreted originating from Al-rich chondrule precursors, while low Cr2 O3 spinels (<0.5 wt.%) are interpreted as CAI-derived material affected by parent body aqueous alteration. Finally, we report a single FgMM with a 16 O-poor composition (Δ 17 O > 0‰ and δ 18 O > +15.0‰). This particle adds to our growing inventory of water-rich C-type asteroid samples united by their formation history which is characterised by accretion of abundant heavy water. Our work strongly supports findings from earlier in-situ O-isotope studies, concluding that small MMs overwhelmingly sample material from CC parent bodies and that CgMMs largely sample chondrules and, to a lesser extent, CAI material. The analysis of CgMMs therefore provides insights into the primitive O-isotope reservoirs that were present in the early solar system and how they interacted.